Migratory cues controlling B‐lymphocyte trafficking in human lymph nodes. Issue 1 (15th September 2020) - Park, Saem Mul; Brooks, Anna ES; Chen, Chun‐Jen J; Sheppard, Hilary M; Loef, Evert Jan; McIntosh, Julie D; Angel, Catherine E; Mansell, Claudia J; Bartlett, Adam; Cebon, Jonathan; Birch, Nigel P; Dunbar, P Rod
Abstract: B‐cell migration within lymph nodes (LNs) is crucial to adaptive immune responses. Chemotactic gradients are proposed to drive migration of B cells into follicles, followed by their relocation to specific zones of the follicle during activation, and ultimately egress. However, the molecular drivers of these processes and the cells generating chemotactic signals that affect B cells in human LNs are not well understood. We used immunofluorescence microscopy, flow cytometry and functional assays to study molecular mechanisms of B‐cell migration within human LNs, and found subtle but important differences to previous murine models. In human LNs we find CXCL13 is prominently expressed at the follicular edge, often associated with fibroblastic reticular cells located in these areas, whereas follicular dendritic cells show minimal contribution to CXCL13 expression. Human B cells rapidly downregulate CXCR5 on encountering CXCL13, but recover CXCR5 expression in the CXCL13‐low environment. These data suggest that the CXCL13 gradient in human LNs is likely to be different from that proposed in mice. We also identify CD68 + CD11c + PU.1 + tingible body macrophages within both primary and secondary follicles as likely drivers of the sphingosine‐1‐phosphate (S1P) gradient that mediates B‐cell egress from LNs, through their expression of the S1P‐degrading enzyme, S1P lyase. Based on our findings, we present a model of B‐cell migration within human LNs, which has both similarities and interesting differences to that proposed for mice. Abstract : Our study shows that in human lymph nodes (LNs) CXCR5 expression by B cells is dynamically regulated. Our data suggest that the migration of B cells into different LN areas is associated with changes in CXCR5 expression, whether during migration of naïve B cells from the high endothelial venules into the perifollicular regions, during localization to primary follicles, during egress via cortical sinuses or during activation and subsequent differentiation processes.